PLTS Off-Grid System Planning for Electricity Needs in Oil Palm Plantations - Rizal, Pep (Universitas Lampung, 2025)
Palm oil plantations are one of the important sectors in the growth of the economy in Indonesia. One of the oil palm plantation areas in the Pasaman Barat Regency is being developed with an estimated land area of 100 hectares. However, due to the location of the land being far from settlements, there is currently no electricity supply that can be used for the operational needs of the land. This research provides a solution for the planning of an Off-Grid solar power plant (PLTS). The method used is a descriptive method with a quantitative research type. Berdasarkan perhitungan, jumlah panel PV yang diperoleh adalah 14 unit, menghasilkan total daya sebesar 2397,89 W, perhitungan kapasitas SCC adalah 35 A, memerlukan kapasitas baterai 12V/100Ah 2 unit, dan inverter 3 kW untuk menghasilkan tegangan AC. The calculation of the Bill of Quantities (BoQ) for material needs amounts to Rp. 21,986,000. This result indicates that the planning of the solar power system is feasible for the long-term operational needs of the plantation, which only requires initial construction capital.